1994
DOI: 10.1136/ard.53.3.158
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between osteoarthritis and osteoporosis in the general population: the Chingford Study.

Abstract: Objective-A total of 979 women from the Chingford general population survey were studied to examine the hypothesis that osteoarthritis (OA) and osteoporosis are inversely related.Methods-All women had radiographs of the hands and knees. A total of 579 also had AP radiographs of the lumbar spine which were graded for the presence of osteophytes. All women had bone densitometry performed at the lumbar spine (L1-L4) and femoral neck. Mean bone densities (BMD) were compared between those with disease and those wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
393
3
13

Year Published

1997
1997
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 452 publications
(435 citation statements)
references
References 17 publications
22
393
3
13
Order By: Relevance
“…The findings showed the global skeletal involvement in OA, being the changes present not only at the affected joints but also in other articular areas. More recent studies have confirmed these findings [20][21][22].…”
Section: Discussionmentioning
confidence: 59%
“…The findings showed the global skeletal involvement in OA, being the changes present not only at the affected joints but also in other articular areas. More recent studies have confirmed these findings [20][21][22].…”
Section: Discussionmentioning
confidence: 59%
“…The hip and knee joints have been most studied, with several groups finding evidence of higher systemic BMD in those with OA at these joint sites in a variety of populations. [7][8][9][10][11] Higher BMD has also been reported in association with OA of the spine 10,12 and hand. 9,10,13 A limitation of cross-sectional studies is that the direction of causality cannot be formally assessed.…”
Section: Bmd and Oa: The Epidemiological Evidence For An Associationmentioning
confidence: 97%
“…These women are derived from the age/sex register of a large general practice in North London. The study design and rationale have been described in detail elsewhere (19). The Guy's and St Thomas' Trust and Waltham Forest Trust Ethics Committees approved the study protocol.…”
Section: Study Subjects the Nottingham Case-control Studymentioning
confidence: 99%